Trends, Problems, and Issues in the Management of Educational Institutions Personnel and Professional Preparation of Education Administration (MURAI: Jurnal Papua Teologi Konstekstual, 2020)
The purpose of this study is: to identify trends, problems and issues in the management of higher educational institutions (HEIs) that arises in Indonesia. To explain the way that personnel and professional in education administration is prepared as a leader. The need to include teachers in the decision-making team, and the development of an organizational system that is based on management thoughts. The area included in this study is education management, administration, and leadership. The method that is employed is a descriptive-qualitative approach with a systematic literature review on education administration and administrators in Indonesia. The results of the research showed that higher education institutions in Indonesia experience constraints related to management capacity, financial and operational systems, as well as deficiencies in standard operating procedures. Identified from a world-class university ranking place, university state and private HEIs, in West Java has not reached satisfaction. One indicator in ranking academic environment, it should be conducive to grow and support intellectual development. The economic crisis and the political instability of Indonesia resulted in failed attempts of implementation of new paradigms in higher education management institutional autonomy and accountability. In administration management, leadership is a key role in the progressing development of an organization.